Wearable and implantable microfluidic technologies for future digital therapeutics - Lee, Sanghoon; Chung, Won Gi; Kim, Enji; Kim, Eunmin; Paek, Joonho; Kim, Dayeon; An, Seung Hyun; Lee, Taekyeong; Lim, Jung Ah; Park, Jang-Ung (Royal Society of Chemistry, 2025)
Microfluidic technology, originally developed for lab-on-a-chip applications, has rapidly expanded into wearable and implantable biomedical systems, enabling precise fluid handling for real-time biosensing, targeted drug delivery, and closed-loop therapeutics. This review provides a comprehensive overview of recent advancements in microfluidic platforms designed for integration with the human body, focusing on both wearable devices and implantable systems. Key design strategies are highlighted, including the integration of microfluidics with soft electronics, wireless communication, and multimodal sensing to enhance mechanical adaptability and functional versatility in dynamic biological environments. In addition, three critical technological directions for advancing digital therapeutics are discussed, particularly focusing on system-level stretchability, multimodal module integration, and artificial intelligence-driven data processing. These capabilities will serve as the foundation for transforming current microfluidic systems into intelligent, autonomous platforms, which will play a pivotal role in shaping future digital therapeutics that are personalized, responsive, and seamlessly integrated into everyday healthcare.